2015
DOI: 10.1161/circep.115.002966
|View full text |Cite
|
Sign up to set email alerts
|

On the Quest for the Best Freeze

Abstract: Background— The second-generation cryoballoon is effective in achieving acute pulmonary vein isolation (PVI) and favorable clinical outcome. To date, no data are available on factors affecting late PV reconnection after second-generation cryoballoon ablation. Methods and Results— A total of 29 consecutive patients (25 male, 86.2%; mean age 57.8±13.8 years) underwent a repeat procedure, after a mean 11.6±4.5 months (range, 3.5–19.7 months)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(35 citation statements)
references
References 20 publications
1
28
1
1
Order By: Relevance
“…Although in our study no significant differences in TIA/stroke have been found between RF and CB ablation procedures, cryoenergy applications have been reported to activate platelets and the coagulation cascade to a lesser degree than RF ablation and lead to a minimal endocardial surface disruption hypothetically resulting in less thrombogenic lesions than those produced with RF energy [30]. Moreover, in our laboratory, cryoballoon ablation procedures are carried out with a significantly shorter LA time than RF ablation procedures [22,25]. The arterial approach might also noticeably contribute to higher rates of vascular adverse events in AF ablation procedures.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although in our study no significant differences in TIA/stroke have been found between RF and CB ablation procedures, cryoenergy applications have been reported to activate platelets and the coagulation cascade to a lesser degree than RF ablation and lead to a minimal endocardial surface disruption hypothetically resulting in less thrombogenic lesions than those produced with RF energy [30]. Moreover, in our laboratory, cryoballoon ablation procedures are carried out with a significantly shorter LA time than RF ablation procedures [22,25]. The arterial approach might also noticeably contribute to higher rates of vascular adverse events in AF ablation procedures.…”
Section: Discussionmentioning
confidence: 53%
“…Complication rates similarly decreased over time in both RF and CB groups. study periods); however, in the latter, the decrease of procedural and fluoroscopy times might also be related to the different cryoapplication strategy of a single 3 minute freeze adopted in the last 366 procedures [22]. No significant differences were observed both in complication rates and in procedural/fluoroscopy times between different operators.…”
Section: Complications In Rf and Cb Groupsmentioning
confidence: 88%
“…12- 14 The consistent application of these TTI-guided ablation protocols, however, is hampered by a limited real-time verification of PV isolation (PVI) when using currently available 15-or 20-mm diameter circular mapping catheters with 8 electrodes. [11][12][13][14] continuous PN pacing was performed using a diagnostic catheter positioned in the superior vena cava (6F; Inquiry TM , St. Jude Medical). PN capture was monitored by tactile feedback of diaphragmatic contraction when the operator's hand was placed on the patient's abdomen.…”
Section: Periprocedural Managementmentioning
confidence: 99%
“…First studies evaluating mapping technologies in conjunction with the hot-balloon, however, are currently under investigation. The TTI independently predicts recovered PV-LA conduction 11 and thereby directly affects arrhythmiafree survival. 12, 18 The direct feedback on freeze cycle efficacy enables the operator to anticipate ineffective freeze cycles, which should result in premature discontinuation of the respective application.…”
Section: Real-time Pv Recordingmentioning
confidence: 99%
“…Как показало наше исследование, частота устойчивой ИЛВ после криоизоляции ЛВ с применением баллона второго поколения достаточно высокаяоколо 70%, что хорошо коррелирует с результатами раннее опубликованных исследований [9][10][11]. В исследовании Ciconte G, et al время до изоляции <60 сек и достижение температуры -40° C в течение 60 сек являлись независимыми предикторами устойчивой ИЛВ [9], а в исследовании Aryana A, et al, выполненного на базе 2 клиник [10], наиболее сильными предикторами оказались время до изоляции ≤60 сек и время до размораживания 0° C ≥10 сек (время до ИЛВ ≤60 сек -ОШ: 1,13 (95% ДИ 1,08-1,19); p<0,001, время до размораживания 0° C -ОШ: 0,62 (95% ДИ 0,49-0,79); p<0,001). В нашем исследовании гипотеза о наличии статистически достоверной разницы для показателя времени до ИЛВ (<60 сек) между группами иЛВ и вЛВ не подтвердилась (ОШ: 1,55 (95% ДИ 0,48-4,97); p=0,459), но возможность контроля регистрации электрической ИЛВ в группе устойчивой иЛВ была значимо больше (ОШ: 3,502 (95% ДИ 1,682-7,289); p=0,001).…”
Section: Discussionunclassified